Cultura organizacional en la Escuela Académica Profesional de Estadística de la Universidad Nacional de Trujillo en el semestre académico 2010-II - Laredo Garcia, John Deyvis (2013)
The present study aims to determine the level of Organizational Culture in the School of Statistics Professional Academic Professional Academic perceived by teachers, students and administrative staff of the school, through the indicators proposed by the accreditation model CONEAU university courses, for which a questionnaire survey of a sample of 170 people between teachers, students and administrative staff. Of these were obtained as a result that the level of organizational culture in Professional Academic School of Statistics in the following dimensions : Level Low ( 21 % ) , level ( 50 % ) , and High ( 29 % ) for students and the same as was obtained for the faculty and staff together had the following dimensions : Level Low ( 20 % ) , level ( 20 % ) and Level High ( 60 % ) which both concentrates the highest degree of concentration on the middle level , these results are represented in Tables and Graphs Descriptive Statistics for applying representations . In the same way we conclude with our diagnosis in the School of Statistics in the 2010- II semester organizational culture is average